Bonnard and the Nabis. - Kostenevich, A. G. (Alʹbert Grigorʹevich) (Temporis collection., 2012)
Pierre Bonnard was the leader of a group of post-impressionist painters who called themselves the Nabis, from the Hebrew word meaning 'prophet'. Bonnard, Vuillard, Roussel and Denis, the most distinguished of the Nabis, revolutionized the spirit of decorative techniques during one of the richest periods in the history of French painting. Influenced by Odilon Redon and Puvis de Chavanne, by popular imagery and Japanese etchings, this post-impressionist group was above all a close circle of friends who shared the same cultural background and interests. An increasing individualism in their art of.